Literature, Literary Criticism and the Historical Index of the Readability of Literary Texts. (2nd July 2016) - Weigel, Sigrid
Abstract: The German scholar Sigrid Weigel takes issue with Professor Zhang Jiang's view on the "correct understanding of a text, " which holds that literary interpretation should be objective and should reflect authorial intention. She raises four points to rebut Zhang's criteria for determining whether an interpretation of literature is correct. Firstly, the central concern of literary interpretation is not authorial intention, but rather the dissection of the creative ideas in the text. Secondly, it is impossible to identify a single objective "authorial intention" when readers' backgrounds, perspectives, methods and purposes vary dramatically. Thirdly, with the concept of the "historical index of readability, " Weigel attempts to establish an optimal meeting point between history and modern interpretive perspectives. Finally, Weigel makes it clear that literature and literary criticism in China today cannot eliminate the influence of Western theories and that the key to the development of Chinese literary theory lies in the combination of tradition and modernity.